Design of A Single-Phase Pure Sine Wave Inverter Using Arduino as The Main Controller - winata, yeriemiaputra; Suprianto, Bambang (Indonesian Journal of Engineering and Technology (INAJET), 2024)
Solar Power Plants (PLTS) have gained popularity in many countries as a clean, cost-effective, and sustainable source of electricity for communities. However, these plants face challenges in converting the electrical current produced by solar panels from direct current (DC) to alternating current (AC), which is widely used by most electrical equipment. In this regard, the role of inverters is crucial. This study aims to design and construct a single-phase pure sine wave inverter using Arduino as the primary controller. The inverter produces a pure sinusoidal output signal with adjustable width using the modulation index and is equipped with a safety system to prevent short circuits between MOSFETs by setting dead time in the Pulse Width Modulation (PWM) signal. The designed inverter output can generate a sinusoidal signal of up to 100 Watts without significant distortion under various loads, with an output voltage of 220VAC ±0.25% and a frequency of 50Hz ±0.10%. While the inverter efficiency reaches 70% across various loads, there is potential to enhance efficiency by incorporating a feedback voltage system and adjusting the carrier frequency. This study has successfully designed and implemented a single-phase inverter that generates a pure sine wave using Arduino as the main controller.  Keyword: Inverter, Pure Sine Wave, Pulse Width Modulation, Arduino